PEMBERDAYAAN KELOMPOK PETANI SAYUR DALAM MENINGKATKAN EKONOMI MELALUI INOVASI PRODUK BAYAM DI DESA REJOSO KIDUL PASURUAN - Ana Kurniawati; Pudji Rahmawati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study discusses the empowerment of vegetable farmer groups through food product innovation in the form of spinach sticks as an economic improvement in Rejoso Kidul Village. This study aims to develop village assets in the form of spinach to improve the economy of the village community. The research method used is called (ABCD) Asset Based Community Development. The strategies that we implement with the community are Discovery (Finding Assets), Dream (Making Dreams), Design (Making Strategies), Define (Deciding on Actions), and Destiny (Monitoring and Evaluation). The results of community empowerment are conducting training in making spinach sticks with vegetable farmer mothers (small groups) in Rejoso Kidul Village.